2021
DOI: 10.1111/aphw.12305
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude and depressive symptoms in Chinese nurses: A longitudinal cross‐lagged study

Abstract: Nurses have a relatively higher rate of depressive symptoms compared to other people. Previous studies have reported that gratitude is correlated with depressive symptoms among healthcare workers. The purpose of this study was to explore the causal relationship between gratitude and depressive symptoms among Chinese nurses. We collected data over 4 months, with 393 nurses at Time 1 and 241 at Time 2. All participants completed online questionnaires. We employed the structural equation models to test the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…Furthermore, this result further supports the broadenand-build theory proposed by Fredrickson [22]. In detail, gratitude can help people alleviate negative emotions [59] and build personal lasting positive resources, such as selfesteem [60], enhance well-being [61] and life satisfaction [62]. These resources are critical to overcoming game addiction for young people.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, this result further supports the broadenand-build theory proposed by Fredrickson [22]. In detail, gratitude can help people alleviate negative emotions [59] and build personal lasting positive resources, such as selfesteem [60], enhance well-being [61] and life satisfaction [62]. These resources are critical to overcoming game addiction for young people.…”
Section: Discussionsupporting
confidence: 81%
“…According to theory and research, gratitude has favorable effects on well-being indicators [17,18]. In the light of recent studies, gratitude appears to be positively correlated with positive affect, happiness, and life satisfaction and negatively correlated with negative affect and depressive symptoms [19,20]. The gratitude list, in which subjects identify three to five items they were grateful for during the day, is one of the treatments that has been most thoroughly applied and studied [21,22].…”
Section: Conceptual Background For the Current Researchmentioning
confidence: 99%
“…An example item is "I am grateful to many people." Previous studies have shown that the GQ-6 exhibits strong reliability and validity (Hao et al, 2022). In this study, Cronbach's alpha coefficient was .764.…”
Section: Gratitudementioning
confidence: 51%
“…Participants rated their extent of agreement with statements using a 7‐point scale ranging from 1 ( totally disagree ) to 7 ( totally agree ). An example item is “I am grateful to many people.” Previous studies have shown that the GQ‐6 exhibits strong reliability and validity (Hao et al., 2022). In this study, Cronbach's alpha coefficient was .764.…”
Section: Methodsmentioning
confidence: 97%